Fibroblast Growth Factor 19 Levels Predict Subclinical Atherosclerosis in Men With Type 2 Diabetes - Hu, Jingyi; Liu, Zhiwen; Tong, Yue; Mei, Zubing; Xu, Aimin; Zhou, Pengcheng; Chen, Xiaoyan; Tang, Weili; Zhou, Zhiguang; Xiao, Yang (Frontiers in Endocrinology, 2020)
Objective: Fibroblast growth factor 19 (FGF19) plays an indispensable role in regulating bile acid, glucose and lipid metabolism, and alterations of its circulating concentration is associated with the development of type 2 diabetes (T2D). Atherosclerosis is directly related to the death-deriving diabetic macroangiopathy in T2D, yet relationships between FGF19 and atherosclerosis in T2D remain unclear. The aim of this study was to investigate the association of circulating FGF19 levels with the development of subclinical atherosclerosis (subAS) in patients with T2D in a 3-year prospective study. Methods: In the present study, 153 newly-diagnosed T2D patients without subAS were recruited at the baseline, and 137 of them completed a 3-year follow-up. FGF19 levels were measured in fasting serum samples collected at baseline and the third-year visits. Carotid, femoral and iliac IMT were detected by high-resolution B-mode ultrasound to determine the presence of subAS. Logistic regression analysis was applied to assess the relationship between serum FGF19 and subAS in patients with T2D. Results: At baseline, serum FGF19 levels were positively correlated with carotid IMT and iliac IMT in men(r = 0.239, P = 0.036; r = 0.309, P = 0.006). At the 3-year follow-up, 25 out of 153 patients developed subAS, and FGF19 levels in men were higher in the subAS group than in the non-subAS group (202.7 [177.9-373.6] vs. 133.4 [85.6-171.3] pg/ml, P = 0.028). Furthermore, in men, higher baseline levels of FGF19 were independently associated with a greater risk of subAS at year 3 in patients with T2D with an odds ratio (OR) of 4.798 per 1-standard deviation (SD) of the FGF19 concentration (OR = 4.798 [95% CI 1.680-13.706], P = 0.003). Baseline FGF19 levels yielded an area under the receiver operating characteristic curve of 0.769 to predict the development of subAS at year 3 in men with T2D. Conclusions: Serum FGF19 levels could help predicting the development of atherosclerosis in men with T2D.